State Plan Proposals 1987-88 Volume II Government of West Bengal - Planning Commission (Planning Commission, 1986)
Heads of Development -Outlay and Expenditure, Development Schemes/Projects - Outlay and Expenditure, Physical Targets and Achievements, Minimum Needs Programme - Outlay and Expenditure, Physical Targets and Achievements - Minimum Needs Programme, Centrally Sponsored Schemes - Outlay and Expenditure, Tribal Sub-Plan - Outlay and Expenditure, Tribal Sub-Plan - Physical Targets and Achievements, Special Component Plan for Scheduled Castes - Outlays, Special Component Plan for Scheduled Castes - Physical Targets.
Government of West Bengal, Development and Planning Department